Does pedicle screw density matter in Lenke type 5 adolescent idiopathic scoliosis?. Issue 2 (January 2018) - Sariyilmaz, Kerim; Ozkunt, Okan; Karademir, Gokhan; Gemalmaz, Halil Can; Dikici, Fatih; Domanic, Unsal
Abstract : Abstract: The aim of this study is to compare the effects of high versus low implant density on correction in Lenke type 5 adolescent idiopathic scoliosis (AIS) patients. A retrospective study of 59 Lenke type 5 AIS patients treated at a single institution were divided into to 2 groups according to implant density. Implant density, preoperative, early postoperative, and last follow-up thoracolumbar/lumbar (TL/L) curves were measured. Thirty-one constructs were high and 28 constructs were low density. The groups were similar in terms of age, sex, Cobb angle, and follow-up time. Mean implant density in low density group and high density group was 75.4% and 96.6%, respectively. High versus low-density comparison showed that there is no significant difference with regard to curve correction in early postoperative and last follow-up periods. The results show that pedicle screw density being low or high, does not affect curve correction rates in the short and long term in our patients.